Vaccination: problems and perspectives. - S. M. Kharit (Журнал инфектологии, 2014)
Massive vaccination had proved its effective morbidity reduction. Today it is necessary to extend vaccination schedule, creation of selective, regional schedules based on epidemiological, clinical, economical substantiation. Development of vaccination needs the profound scientific research, modernization of adverse reaction observing system, betterment training system and awareness of population.